“I Want to be an Entrepreneur”: The Important Role of Effectiveness of Entrepreneurship Education and Internal Locus of Control - Ardyan, Elia; Ivan, Johanes; Parega, Erwin; Suade, Yuyun K. M.; Hutapea, Dina Martha; Susanti, Ari (Jurnal Entrepreneur dan Entrepreneurship, 2021)
This study examines the effectiveness of entrepreneurship education, entrepreneurial social support, and internal locus of control in increasing entrepreneurial intention. This research was conducted at S1 Management students at Ciputra University Surabaya (class of 2016). The total number of respondents in this study was 92 students. The analysis used is partial least square structural equation modeling (SEM-PLS). Data were processed using WarlPls version 7. The results of this study indicate that entrepreneurial social support and the effectiveness of entrepreneurship education can improve internal locus of control. High internal locus of control will have an impact on student's intention to become entrepreneurs as their career choices. Other results also show that the effectiveness of entrepreneurship education is an important part of increasing entrepreneurial intention compared to entrepreneurial social support factors.